Remote estimation of pulse wave features related to arterial stiffness and blood pressure using a camera. (February 2021) - Djeldjli, Djamaleddine; Bousefsaf, Frédéric; Maaoui, Choubeila; Bereksi-Reguig, Fethi; Pruski, Alain
Abstract: Recent technological advances in the field of sensors, signal processing and image processing favor the development of new techniques for vital parameters monitoring such as imaging photoplethysmography (iPPG). iPPG is a simple and noninvasive measurement technique. It has been employed to remotely estimate heart and respiratory rates, oxygen saturation and blood pressure through the measurement of blood volume pulse using a camera. In the recent decades, researchers used the morphology of contact photoplethysmographic (cPPG) signal for the assessment of arterial stiffness, blood pressure, arteriosclerosis, cardiac output, and vascular aging. We propose to study, in this article, the similarities between iPPG and cPPG waveform features that are associated to cardiovascular diseases. A fast camera and contact probes were respectively employed to record iPPG and cPPG signals. Their waveform features such as time, areas, amplitude and second derivative features were then extracted and analyzed. Results show a high correlation between the two measurement techniques. This research opens several perspectives in the remote assessment of blood pressure and arterial stiffness, and therefore for non-contact diagnosis of several cardiovascular diseases. Highlights: A camera-based method is proposed to extract and analyze 16 pulse wave features. The extracted features are associated to blood pressure and arterial stiffness. Image and signal processing techniques were proposed to properly extract the features. The experiences were conducted on 12 healthy subjects under two breathing conditions. Results showed high agreement with the features recorded by reference sensors.